Developing a Professional Competence Model for Management Education. Final Report to the National Institute of Education, Research Report Number Ten. [Revised.] - Mentkowski, Marcia; Alverno Coll., Milwaukee, WI. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
Abilities needed for effective managerial performance were identified and sequenced to improve the management curriculum at Alverno College. Performance, perceptions, and careering and professional development of 103 women managers and executives from 53 Milwaukee private corporations were evaluated using a performance measurement system. A managerial competence model was developed, and over 500 behavioral examples of managerial abilities were identified based on particular job contexts. Using the Behavioral Event Interview, managers identified behaviors they judged to be critical to their job performance. Competencies demonstrated by the managers were coded for frequency, and the developmental sequence of the skills was determined. The Behavioral Event Interview Writeup was used to translate the information from the oral interview to a form for coding competencies. The Management Performance Characteristics Inventory was used to rate abilities descriptive of outstanding managers and average managers. In addition, the Management Careering Questionnaire was administered to obtain information on the managers' position, experience and advancement, success/satisfaction, education, personal roles and socialization. The results of the study, methodological information, and the study questionnaires and forms are presented. (SW)
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Contract Number: NIE-G-77-0058.
ERIC Note: For related documents, see HE 018 004 and ED 239 557-565. This document supersedes ED 239 566.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Attitudes; Administrator Role; Business Administration Education; Career Ladders; Competence; Educational Background; Employment Experience; Females; Higher Education; Job Performance; Job Satisfaction; Management Development; Models; Questionnaires; Skill Development; Work Environment; Alverno College WI; Wisconsin (Milwaukee) -- Women Administrators; Reports, Research; Tests/Questionnaires.